Effect of Blood Transfusion on the Outcome of Cardiac Surgery Patients at Benghazi Medical Center (2014-2017) - Eltajuri , Nuria Mohammed Ali; Meidan, Tunis M. (Scientific Journal of University of Benghazi, 2022)
Background: The effect of blood transfusion on cardiac surgery patients is dependent on other factors such as demographics, type of open heart surgery and hemoglobin level before surgery. Aims: to determine the risk factors that lead to a blood transfusion during cardiac surgery, and to find out the effect of blood transfusion on mortality in cardiac surgery patients. Methods: A cross-sectional survey study that included 240 patients who underwent cardiac surgery between 2014 and 2017 in Benghazi. All the data was collected from adults (≥ 18 years). The association between blood transfusion in patients of cardiac surgery and other pre-operative variables was assessed using the Chi-square test. Descriptive statistics such as mean, mode, median and standard deviation were used. Results: The database included 240 patients whose mean age was 57.9 ± 11.5 years and the male-to-female ratio was 2:1. 197 (82%) patients underwent a coronary artery bypass graft, 178 (74.2%) were anemic, and 74 (30.8%) patients received blood. The mortality rate was 9.2%. The outcome of surgery according to blood was statistically significant( p< 0.003). Conclusion: The outcome of cardiac surgery is affected by blood transfusion. There is no relation between blood transfusion and other factors ( age, sex, type of surgery, hemoglobin level of patients) in cardiac surgery